Masticatory muscle changes on magnetic resonance imaging of dogs with Neospora caninum compared to meningoencephalitis of unknown origin - Zilli, Jessica; Fleming, Kathryn; Fisher, Chloe; Sparks, Tim; Harcourt-Brown, Tom; Ives, Edward (Frontiers in Veterinary Science, 2025)
Infectious meningoencephalitides represent an important differential diagnosis for meningoencephalitis of unknown origin (MUO) in dogs. Treatment of the latter requires immunosuppression, but laboratory test results for infectious agents may take several days to return. This study investigated whether the presence of masticatory muscle changes on magnetic resonance imaging (MRI) of the head can be used to distinguish dogs with neosporosis from those with MUO at the time of diagnosis. Cases diagnosed with neosporosis or MUO at two referral centers in the United Kingdom (UK) were retrospectively collected. Clinical data were reviewed, and each MRI study was blindly assessed by a radiologist, a neurologist, and a neurology resident for the presence of masticatory muscle changes by consensus opinion. Statistical analysis was performed on obtained data. Twenty-two neosporosis cases and 23 MUO cases were enrolled. In the neosporosis group, six dogs (27%) had masticatory muscle changes, compared to one dog (4%) in the MUO group (p = 0.047). All six neosporosis cases had bilateral, multifocal, T2W and FLAIR hyperintense, contrast enhancing muscular changes, with three having concurrent masticatory muscle atrophy. The only MUO case with muscle changes had a mild, focal, unilateral temporal muscle lesion which was only visible in the T1W post-contrast images. Within the neosporosis group, dogs with masticatory muscle lesions had significantly higher cerebrospinal fluid WBC counts (p = 0.017) and protein concentrations (p = 0.025) compared to those without muscle changes. In conclusion, characteristic bilateral, multifocal masticatory muscle changes should raise the index of suspicion for neosporosis in dogs with an imaging diagnosis of meningoencephalitis and starting early antimicrobial treatment is recommended. However, the absence of masticatory muscle abnormalities does not exclude active Neospora caninum infection. In these cases, whether immunosuppressive or antimicrobial treatments are started prior to receiving further test results should still be based on the clinical status of the animal and index of suspicion using a combination of all available clinical information at that time.